Inscription and interpretation of text: a cultural hermeneutic examination of virtual community - Gary Burnett; Michael H. Dickey; Michelle M. Kazmer; Katherine M. Chudoba (Information Research: An International Electronic Journal)
People engaging in electronic exchanges can create communities--places with socially constituted norms, values, and expectations. We adopt an anthropological perspective, yoked with a methodology based in hermeneutics, to illustrate how language use both reflects and influences culture in a virtual community. Our study analyses contributions to a Usenet newsgroup. Four elements of our conceptual model--coherence, reference, invention, and intention--provide mechanisms to examine a community's texts as it engages in social interaction and knowledge creation. While information exchange and socializing are intertwined, our model allows a robust understanding of the relationship between the two. Texts are not merely vehicles for communication but serve multiple purposes simultaneously. While they transfer information, texts also provide information within a social context, and create an expanding archive of socially-contextualized information well beyond the capabilities of any individual participant. This allows groups to negotiate reputations, socialize, and define the limits of their knowledge.